Discovery of potent heat shock protein 90 (Hsp90) inhibitors: structure-based virtual screening, molecular dynamics simulation, and biological evaluation - Yonghua Xu; Yunting Zou; Shasha Zhou; Miao-Miao Niu; Yan Zhang; Jindong Li; Zhen Xu; Li Yang (Taylor & Francis Group, 2023)
Heat shock protein 90 (Hsp90) is considered an attractive therapeutic target for cancer treatment due to its high expression in many cancers. In this study, four potent Hsp90 inhibitors (HPs 1-4) were identified using structure-based virtual screening. Among them, HP-4 exhibited the most potent inhibitory effects (IC50 = 17.64 ± 1.45 nM) against the Hsp90 protein, which was about 7.7 times stronger than that of MPC-3100 (a positive inhibitor targeting Hsp90). In vitro cytotoxicity assay suggested that HP-4 could effectively inhibit the proliferation of a series of tumour cells, including HCT-116, HeLa, A549, A2780, DU145, HepG2 and A498. Furthermore, in vivo assay displayed that HP-4 had significant anti-tumour effects on HCT-116 cell-derived xenograft models. These data demonstrate that HP-4 could be a potential lead compound for the further investigation of anti-tumour drugs.